Factors affecting the cold flow properties of biodiesel: Fatty acid esters. Issue 5 (4th March 2018) - Yang, Chao; He, Kangkang; Xue, Yuan; Li, Yong; Lin, Hualin; Sheng, Han
ABSTRACT: Biodiesel is renewable, sustainable, and cost-effective; it possesses good lubricity and high cetane number. Nevertheless, its poor cold flow properties impede the popularization and application of biodiesel. In this study, the cold flow properties of peanut and rapeseed biodiesel and their blends with different fatty acid esters were investigated, including different chain lengths (saturated and unsaturated), different double bond numbers, and different alcohol chains. Results showed that shorter chain length, more double bonds, and branched alcohol chain could effectively improve the biodiesel cold filter plugging point (CFPP). This study also tried to explore the mechanism action of this phenomenon.